Sistem Pendukung Keputusan untuk Pemilihan Platform Pengembangan Aplikasi Web Menggunakan Metode MOORA - Reflan Nuari (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2024)
A web application development platform is a framework or environment that provides tools, libraries, and features to simplify the process of creating a web-based application. Choosing a web application development platform is an important step that affects the success of an application development project. Each platform has its own advantages and disadvantages, such as scalability, ease of integration, security level, cost efficiency, and ease of use. However, without a systematic approach to evaluating and comparing these alternatives based on relevant criteria, the risk of choosing a suboptimal platform is increasing. The purpose of this research is to apply DSS in the selection of web application development platforms using the MOORA method which provides an objective and structured solution in choosing the platform that best suits the needs of web application development based on various criteria. By using the MOORA method, it is hoped that it can produce recommendations that are appropriate and acceptable to developers and stakeholders in the decision-making process. As a result of the calculation using the MOORA method, react ranks first with a final value of 0.4265, making it the best platform for web application development in this case. Angular follows in second place with a value of 0.4261, which indicates a performance that is almost on par with React. Laravel is ranked third with a value of 0.4142, followed by Django in fourth place with a value of 0.4095. Vue.js ranks fifth with a value of 0.3902, while Ruby on Rails is in last place with a value of 0.3756. The results of this ranking reflect the excellence of React in meeting the set criteria, followed by other alternatives that have strong performance in certain aspects.